2021
DOI: 10.1111/ijfs.15111
|View full text |Cite
|
Sign up to set email alerts
|

Functional compounds in dragon fruit peels and their potential health benefits: a review

Abstract: Summary Recovery of bioactive or functional compounds from fruit wastes is a current research trend, not only to lessen the waste disposal burden, but also to meet the increasing demand from the public for health‐beneficial plant‐based products. In this review, the main groups of functional compounds from dragon fruit peels including betalains, phenolics and dietary fibres are comprehensively scrutinised. The potential health benefits of these phytochemicals in individuals or in matrices are discussed, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 66 publications
(74 reference statements)
2
26
1
4
Order By: Relevance
“…Both peel and flesh samples exhibited a decrease in total phenolic amounts after 5 min of sonication. Similar reduction in fruit juice with sonication for a long time was reported by Le & Le (2021). The exposing to ultrasound for a long time and high sonication wave could lead to form of the more reactive oxygen species, which oxidised the phenolics and caused loss of antioxidants (Yeoh & Ali, 2017).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Both peel and flesh samples exhibited a decrease in total phenolic amounts after 5 min of sonication. Similar reduction in fruit juice with sonication for a long time was reported by Le & Le (2021). The exposing to ultrasound for a long time and high sonication wave could lead to form of the more reactive oxygen species, which oxidised the phenolics and caused loss of antioxidants (Yeoh & Ali, 2017).…”
Section: Resultssupporting
confidence: 70%
“…For flesh of pitaya, the catechin contents reached their maximum levels when sonicated for 30 min under atmosphere condition (8.35 mg per 100 g), and sonicated for 5 min under vacuum (9.35 mg per 100 g). Ultrasound-assisted extraction had effect on phenolic compounds probably due to change in enzyme activities (Le & Le, 2021). Moreover, gallic acid content of flesh remained constant after sonication process.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These bioactive compounds regulate glycaemic response, lipid accumulation in liver, reduce inflammation and growth of foodborne pathogens due to high radical scavenging abilities and modulation of gut microbiota (Song et al ., 2016; Zambrano et al ., 2019; Saenjum et al ., 2021). More recently, it has been found that pitaya fruit has beneficial effects on gut microbiota (Pansai et al ., 2020) owing to the presence of bioactive ingredients in its pulp or the outer parts (Le, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the modern fast‐paced life, improper diets result in an increasing incidence of many chronic metabolic diseases, such as obesity and diabetes caused by high‐sugar and high‐fat diet, and gout caused by high‐purine food. In recent years, there has been growing role and demand of food nutrition in human health (Le, 2021). Consumers no longer only pursue the characteristics of food itself, such as colour, aroma and taste, but pay more attention to its nutritional and health‐promoting properties.…”
mentioning
confidence: 99%